2020
DOI: 10.1111/jfbc.13393
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of quality and bioactive compounds in pomegranate fruit (Punica granatumL.) by combined application of organic acids and chitosan edible coating

Abstract: Pomegranate is a subtropical fruit that affects its cold storage. To ameliorate chilling injury, fruits were treated with malic acid (50 and 100 mM MA) and oxalic acid (5 and 10 mM OA), and then, coated with 2% chitosan (CH) and stored at low temperature (2°C) for 4 months. Treatments significantly delayed the development of browning signs and reduced malondialdehyde and hydrogen peroxide of arils as compared to control. CH+ 5 mM OA resulted in the highest catalase activity in arils during storage. Anthocyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…A decreasing trend in the TPC of untreated pomegranate fruit during cold storage has been reported in several studies [13,17,27]. The decrease in TPC is related to phenolic degradation due to enzymatic activities of polyphenol oxidase and peroxidase due to low temperature stress [17,82]. Application of treatments GA MS + Liner 1, GA MS + Liner 2 showed the greatest response in fruit to reduce the loss of TPC during storage.…”
Section: Total Soluble Solids and Titratable Aciditymentioning
confidence: 78%
See 2 more Smart Citations
“…A decreasing trend in the TPC of untreated pomegranate fruit during cold storage has been reported in several studies [13,17,27]. The decrease in TPC is related to phenolic degradation due to enzymatic activities of polyphenol oxidase and peroxidase due to low temperature stress [17,82]. Application of treatments GA MS + Liner 1, GA MS + Liner 2 showed the greatest response in fruit to reduce the loss of TPC during storage.…”
Section: Total Soluble Solids and Titratable Aciditymentioning
confidence: 78%
“…The authors attributed the increase to continued biosynthesis and accumulation of anthocyanins induced when fruit were subjected to cold storage temperatures [46]. The decreasing pattern observed between day 35 and day 42 could be related to phenolic degradation due to enzymatic activities of polyphenol oxidase and peroxidase [17,82]. Sayyari et al [83] similarly observed decrease in TPC in 'Mollar de Elche' pomegranate fruit during 84 days of cold storage (2 • C).…”
Section: Total Soluble Solids and Titratable Aciditymentioning
confidence: 97%
See 1 more Smart Citation
“…It was revealed that CH could induce PAL activity and decrease tissue browning by inhibiting the activity of PPO in sweet cherry fruits (Dang et al, 2010). In pomegranate fruits treated with CH plus malic and oxalic acid, low browning signs as result of low activity of PPO were observed during the 120 days of cold storage (Ehteshami et al, 2020).…”
Section: Phenols Metabolismmentioning
confidence: 99%
“…Moreover, the difference between Δ L * of the FWN treated with Mal and Asp was obvious with the decrease in pH value. Malic acid and oxalic could reduce the browning of pomegranate by inhibiting the PPO and POD activities (Ehteshami et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%